Motivação no trabalho voluntário: expectativas e motivos na Pastoral da Criança - Cavalcante, Carlos Eduardo (2012)
The present study has proposed a structural model to identify the reasons why individuals become voluntary, keep and exit this type of work. The empirical space was the Pastoral da Criança - social action agency of the National Conference of Bishops of Brazil (CNBB) - community-based institution that has its work based on solidarity and the sharing of knowledge. The theoretical framework has the context in which are volunteering studies in Brazilian and world level. Then discuss the various concepts of volunteering and presented the theoretical models of volunteer motivation. Studies of Mostyn (1983) and studies conducted by the BEPEGE-Base for Studies and Research in Management Policies and Strategies - in their line of research GERQUAL - Human Resource Management and Organizational Quality - of the Federal University of Rio Grande do Norte as Carvalho e Souza(2006), Souza, Medeiros e Fernandes (2006), Souza et al (2009, 2010), Cavalcante et al (2011a, 2011b, 2011c, 2011d) were the main theoretical references for the construction of the model that was tested. Data collection was done through a survey with 71 indicators, in 2 visits to cities from the Diocese of Pesqueira, Pernambuco. The first data collection occurred in the period between May 30 and June 3, 2011, in Buique/PE and the second collection happened in Pesqueira/PE, in St. Joseph Seminary, in the period between July 6-8, 2011. 720 questionnaires were collected. The sample was divided into two parts. Exploratory Factor Analysis was applied in first part and Confirmatory Factor Analysis - structural equation modeling - in the second half. The examination of the results achieved by the expectations, reasons for entry, reasons for staying and exit reasons showed that all hypotheses were accepted. So the motivation of voluntary Pastoral da Criança can be explained by a set of interactions between these five constructs: Altruistic, Affectionate, Amiable, Adjusted and Astute